كدليل حيوي لتراكم بعض العناصر الثقيلة في هور ابي زرك جنوب العراق ypha domingensis استخدام النبات المائي - آفاق طالب فرهود (University of Thi-Qar Journal of Science, 2019)
The present study was conducted during the winter and summer of 2016 to study the bioaccumulation of some heavy metals and the use of (Typha domingensis )as bioindicator to the accumulation of these elements through the food chain (water - sediments - aquatic plant) at three stations in Abu-Zariq Marsh - southern Iraq.       Three heavy elements (Cd, Cu, Pb) were used in this study. The elements were studied in the dissolved and particulate phases of water, sediment and  aquatic plant (T. domingensis), the bioconcentration factor B C. F was calculated for the above studied elements in the aquatic plant tissue, which was as follows: (34867, 26719 and 13333) once as concentrated in water respectively   The study concluded that the concentrations of the studied elements in the sediments are higher than in the water with dissolved phase , particulate phase and aquatic plant , as follows: Sediments> aquatic plants (T. domingensis) > particulate part > Dissolves part of water . The abundance of elements is as follows: pb > Cu> Cd. In the water of its phases, sediments and aquatic plants, the concentration of metals are effects with  change in the seasons of the year, human activities and climatic factors is affected. This plant have a great ability to accumulate heavy elements and considered a good biological indicators for this type of pollutants.             أجريت  الدراسة  الحالية خلال شتاء وصيف /  2016  لدراسة التراكم الحيوي لبعض العناصر الثقيلة واستخدام  النبات البردي Typha domingensis  كدليل حيوي لتراكم هذه العناصر  من بعض مكونات النظام البيئي (ماء – رواسب –  نبات مائي ) في ثلاث  محطات في هور ابي زرك – جنوب العراق .        تم استخدام ثلاث عناصر  ثقيلة ( Cd, Cu , Pb)  في هذه الدراسة ، اذ درست العناصر في الطورين الذائب والعالق من الماء والرواسب وأنسجة نبات البردي   domingensis . T ، تم حساب معامل التركيز الاحيائي B. C. F   للعناصر المدروسة أعلاه في انسجه النبات والذي كـان كالأتي :( 34867 و 26719 و 13333) مره بقدر تركيزها في الماء على التوالي.     استنتج من الدراسة ان تراكيز العناصر المدروسة في الرواسب  أعلى مما هو عليه في الماء بجزيئة الذائب و العالق للماء والنبات المائي  وكان ترتيب العناصر  ، كالأتي : الرواسب >النبات المائي  (البردي) > العالق > الذائب . وترتيب الوفرة للعناصر في الماء بطوريه  و الرواسب والنبات المائي كالأتي : الرصاص >  النحاس > الكادميوم . استنتج من الدراسة ان تراكيز العناصر تتأثر  في التغايير في فصول السنة والانشطة البشرية والعوامل المناخية  , ولهذا النبات قدرة كبيره لمراكمة  العناصر الثقيلة ,  ويعتبر كدليل حيوي جيد لهذا النوع من الملوثات .              ت .